Network directional distance function for measuring performance of water utilities in Malaysia / Norbaizura Kamarudin ... [et al.] - Kamarudin, Norbaizura; Khairudin, Zuraida; Awang, Nur Ainina; Mohd Rashid, Nur Rasyida; Derasit, Zuraidah (UiTM Cawangan Perlis, 2025)
Evaluating the performance of water supply services is crucial in many countries. Performance indicators (PIs) are often used to check how well water management is working. One important PI is the percentage of Non-Revenue Water (NRW), which shows how much water is being lost and how efficiently the utility is using water. Lower NRW percentages reflect better performance. NRW happens while delivering the water supply to the consumer; hence, NRW can be classified as an undesirable output in the water supply process. One type of Data Envelopment Analysis (DEA) model that directly considers the undesirable output factor is the Directional Distance Function (DDF) model. Recently, researchers have expanded the DEA and DDF models into network structures. Since the process of supplying the water services can be expressed as a network process, this study attempts to use the Network Directional Distance Function (NDDF) to measure the water utilities’ performance that incorporates NRW as the undesirable output factor. Additionally, it proposes an alternative performance indicator for benchmarking Malaysian water utilities. The study used 2015-2016 data from the Suruhanjaya Perkhidmatan Air Negara (SPAN) on 14 Malaysian water utility providers. Results show that only Johor and Pulau Pinang were consistently efficient under both DDF and NDDF models. The NDDF model provided clearer efficiency rankings, identifying three efficient states across both years, whereas the DDF model found five in 2015 and seven in 2016. These findings suggest that NDDF enhances performance evaluation and ranking, helping authorities benchmark top-performing utilities for better water service management in Malaysia.